The Plutonomy of the 1%: Dominant Ownership and Conspicuous Consumption in the New Gilded Age - Tim Di Muzio (Millennium: Journal of International Studies, 2015)
This article offers a study on the plutonomy of dominant owners and what their consumptive practices might tell us from the lens of the capital as power framework in IPE. I argue that the differential consumption of dominant owners is an important dimension of an internationalised capitalist mode of power for two reasons. First, Nitzan and Bichler argue that the primary driver of accumulation is the desire for differential power symbolically expressed in a magnitude of money. In this article, I argue that there is a secondary dimension noted but underdeveloped in their framework and influenced by Veblen: the drive for social status and the display of positionality through differential intraclass consumption. Second, as identified by Kempf, I argue that the consumptive practices of dominant owners are helping to lock global society into an unsustainable and ethically indefensible quest for perpetual economic growth. This growth project not only undermines calls for needed social and economic change but also threatens populations with environmental collapse.
Keywords: 330; 1%; capital; consumption; dominant owners; IPE; New Gilded Age; plutonomy